Validação do questionário thypro-39br e desenvolvimento de aplicativo para avaliar a qualidade de vida em pacientes com doenças da tireoide - Freitas, Jonatas Catunda (2021)
Introduction: ThyPRO-39 is the quality of life questionnaire for thyroid diseases most used, better than generic questionnaires because addresses specific thyroid diseases aspects and superior to other specific questionnaires for its wide capacity to cover different diseases, benign and malignant, and at different treatment stages. Objectives: to validate the Brazilian Portuguese translation of the ThyPRO-39 questionnaire, to analyze the quality of life of patients with thyroid disease, and to develop an app to calculate the questionnaire score. Methodology: The Portugal Portuguese version of ThyPRO-39 was provided by the questionnaire creator, were made some changes to adapt it to Brazilian Portuguese and these changes were validated by a translator specialized in portuguese with scientific knowledge. A cross-sectional study was carried out on people with any thyroid disease, who were invited to participate in the research through social media. Each participant accessed the link, accepted the research terms and answered 2 quality of life questionnaires, SF-36 and ThyPRO-39. The ThyPRO-39br questionnaire was validated using 3 complementary techniques: convergent validation with SF-36, internal consistency validation and clinical validation. Results: Data collection was carried out between August 2020 and October 2020 and included 516 participants from all over Brazil, the state of São Paulo with the highest proportion (29.3%), 95.3% were female, mean age of 37 years, mean BMI 27.7, 58.1% undergoing thyroidectomy, 49% diagnosed with thyroid cancer. The comparison of the results obtained in the 2 questionnaires, showed moderate correlation in the most similar scales, Cronbach's alpha was greater than 0.7 in 10 of the 12 scales and was very close in the two in which it did not reach this value, hyperthyroidism symptoms (0.647) and eye symptoms (0.688). Conclusion: The Brazilian version of ThyPRO-39 has been satisfactorily validated and is available for future research on quality of life in thyroid diseases. The participants in the present study had scores of quality of life much worse than the results reported in other similar studies, being more intense in overweight people and in those who do not practice physical activity. “Tireoide” app was developed and is available for download on Android platform to facilitate questionnaire usage on a daily basis by patients and health professionals.